Terceiro setor em HIV/AIDS: mapeando o ativismo social na contemporaneidade - Farias, Maio Spellman Quirino de (2006)
The struggle against AIDS is a kind of action in favor of life and the organized Brazilian civil society incorporated it in a meaningful dimension. This struggle matured the creation of non-governmental organizations (NGOs) and advanced with the discoveries about the disease. Since the very early 90 s, the consolidation of the partnership involving the movement anti-aids with State came up with a dilemma for the entities of civil society: are they just executors of governmental policies or do they take up the role of effective demands concerning public policies? Since then, activism against aids started to stand for execution of projects and one considers that the institutional way of anti-aids work has problems because it constructs a basic strategy to take off the political aspect of the third sector. The NGOs/aids consolidate the reconfiguration of capital and get far from street activities. This is important to be studied because the relationship between society and aids, contemporarily, can prevent them from accomplishing their agenda referring to political mobilization and collective resistance. This research started to be carried after some visits, previously arranged, to an institutional life support group called Grupo de Apoio à Vida-GAV, in Campina Grande. A semi-structured interview was applied to 31 users and to 6 technicians of the entity mentioned. One aimed at investigating the activist anti-aids practice, identifying the conceptions of activism and knowing how social actors assess those practices. Preliminary results indicate that one of the conceptions on activism among the interviewees refers to the execution of projects through partnership of NGOs and supporting institutions, governmental or non-governmental. Although this new conception on activism consolidates a non-political aspect, there are other ways of executing projects and participating actively, according to some users, such as: meetings, lectures and other sorts of events promoted by the group, which are also legitimate actions representing anti-aids activism at the present context